Firms, Trade and Profit Shifting: Evidence from Aggregate Data - Sébastien Laffitte; Farid Toubal (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using aggregate data on U.S. multinational firms' activities, we document the impact of tax havens on the organization and trade of multinational firms. Conventional wisdom says that MNEs set up foreign sales platforms close to large markets to benefit from the proximity to consumers. We show, both theoretically and empirically, that the tax environment plays an important role in explaining the location of the foreign sales platforms. We document that foreign sales platforms in tax havens fuel profit shifting especially in services industries. We shed lights on the attractiveness of different tax havens for distinctive sectoral activities. The back-of-the-envelope computation shows that profit shifting by foreign sales platforms in tax haven amounts to 83bn in 2013.
Keywords: F23; H26; 330; foreign platforms; tax havens; profit shifting; firms' organization